Loss and Light in El Salvador. - Malone, Matt (America Magazine: The Jesuit Review of Faith & Culture, 2020)
The article offers information on El Salvador, the smallest country in Latin America. Topics discussed include increase in crime rates since a 2012 high, when El Salvador was rated the most violent country on earth; the Gloria Kriete Foundation for aid, established in 2014 by the seven surviving children of the late Mrs. Kriete; and Kodigo Programming Academy for programming and software development and developing the character of students by teaching values-based decision making.